(untitled) (Research, Society and Development, 2022)
Introduction: Cervical cancer diagnosed during pregnancy is uncommon, and there are risk factors for this condition, such as lack of access to health services and failure to perform the recommended screening for early diagnosis of precursor lesions of cervical cancer. cervix. In young patients with fetal maturation, the treatment is radical hysterectomy with bilateral pelvic lymphnodenectomy, preceded by cesarean section. We report on a 33-year-old female patient who was diagnosed with an early-stage invasive squamous cell carcinoma in the course of a 26-week pregnancy. After discussion with the couple, it was decided to wait for fetal maturation and the pregnancy would be terminated at the 36th week by cesarean section, followed by radical hysterectomy and bilateral pelvic lymphadenectomy. Methods: This is a retrospective, cross-sectional, qualitative and descriptive observational study. This work was approved by the Research Ethics Committee of the State University of Piauí, with CAAE n. 30154720.0.0000.5209. Final considerations: The case reported and the publications found in the literature show agreement on the possibility of having a peaceful pregnancy with cervical carcinoma without harm to the fetus if follow-up and adequate treatment are carried out. Although both surgical treatment and local and systemic treatment have advantages and disadvantages, both for the fetus and for the mother, it is necessary to have a multidisciplinary team available so that, according to the individuality of the case, follow-up can be carried out. and help in making the best decision for the maternal-fetal set, the case reported and publications raised show that it is possible to have a peaceful pregnancy with cervical carcinoma without harm to the fetus if follow-up and adequate treatment are carried out.